2022
DOI: 10.3390/ijerph20010393
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Patterns with Type 2 Diabetes Mellitus: A Cross-Sectional Study Based on Latent Class Analysis

Abstract: Sleep duration, sleep quality and circadian rhythm disruption indicated by sleep chronotype are associated with type 2 diabetes. Sleep involves multiple dimensions that are closely interrelated. However, the sleep patterns of the population, and whether these sleep patterns are significantly associated with type 2 diabetes, are unknown when considering more sleep dimensions. Our objective was to explore the latent classes of sleep patterns in the population and identify sleep patterns associated with type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…This approach should involve interventions such as meditation, improving sleep patterns, cultivating social support networks, and providing psychological support. [21][22][23][24] Recognizing the need for these interventions is crucial in effectively managing diabetes.…”
Section: Tablementioning
confidence: 99%
“…This approach should involve interventions such as meditation, improving sleep patterns, cultivating social support networks, and providing psychological support. [21][22][23][24] Recognizing the need for these interventions is crucial in effectively managing diabetes.…”
Section: Tablementioning
confidence: 99%
“…Diperkirakan sekitar 462 juta orang atau setara dengan 6,28 % populasi dunia terkena diabetes mellitus tipe 2 sejak tahun 2017 dan diproyeksikan terus meningkat menjadi 7.079 orang per 100.000 penduduk pada tahun 2030 (Khan et al, 2020;Setyawati et al, 2020). Tingginya kasus diabetes mellitus merupakan faktor risiko independen terhadap gangguan tidur, gejala cemas, dan berdampak pada kualitas hidup yang buruk (Dong et al, 2020;Liu et al, 2023).…”
Section: Pendahuluanunclassified
“…Healthy behaviors have beneficial impacts in reducing cardiovascular disease and mortality [6,7]. Several studies have suggested an association between cardiovascular disease and unhealthy lifestyles, such as sedentary behavior [8], unhealthy dietary behavior [9], and unhealthy sleep patterns [10].…”
Section: Introductionmentioning
confidence: 99%